Strategic insights into development of information system using Zachman Framework / Nur Fara’Ain Ebbie Izman - Ebbie Izman, Nur Fara’Ain (2017)
This paper illustrates the possibility of using Enterprise Architecture as an indicator that provide guidance in development and documenting an Information System. To address the problem regarding development information system, this research examine from course based project of students in Bachelor of Information Technology (Hons.) Information Systems Engineering (ISE) where there is no integrated perspective of their project artifacts especially in the three consecutive core courses that represent (ITS470, ITS570 & ITS670) the development phases of the project. The courses are taken in three consecutives semesters. Because there is no tool to assist the low holistic understanding for the three courses, failures among students for the related courses are high. Hence, the intention in this research is to establish an Enterprise Architecture for an integrated view to understand the holistic artifacts relationship of the Information System developed. The research is divided into three different phases of Knowledge Acquisition, Data Gathering & Analysis and Data Interpretation. Zachman Framework was chosen to relate and map the system development phases and their artifacts. A complete student project is selected and output documents SRS, SDD and STD are the source for analyzing to provide as a case study in this research. The blueprints of selected information system is constructed and implemented using guidelines from Pereira and Sousa (2004).